2018
DOI: 10.1107/s1600576718008786
|View full text |Cite
|
Sign up to set email alerts
|

Ni/GeSn solid-state reaction monitored by combined X-ray diffraction analyses: focus on the Ni-rich phase

Abstract: The Ni/Ge 0.9 Sn 0.1 solid-state reaction was monitored by combining in situ X-ray diffraction, in-plane reciprocal space map measurements and in-plane pole figures. A sequential growth was shown, in which the first phase formed was an Ni-rich phase. Then, at 518 K, the mono-stanogermanide phase Ni(Ge 0.9 Sn 0.1 ) was observed. This phase was stable up to 873 K. Special attention has been given to the nature and the crystallographic orientation of the Ni-rich phase obtained at low temperature. It is demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Although no data about the Ni-Ge-Sn ternary system or the Sn solid solubility in Ni-Ge intermetallics is available in the literature, a hypothesis can be drawn from the observed behavior. The Ni-rich phase was verified to correspond to the " hexagonal phase in the Ni/GeSn system (Quintero et al, 2018b) as for the Ni/Ge system (DeSchutter et al, 2016). This latter is nonstoichiometric and can accept a wide range of Ge concentration between 35 and 44%; a similar behavior is expected for GeSn.…”
Section: Incorporation Of Sn Into the Intermetallicsmentioning
confidence: 93%
See 2 more Smart Citations
“…Although no data about the Ni-Ge-Sn ternary system or the Sn solid solubility in Ni-Ge intermetallics is available in the literature, a hypothesis can be drawn from the observed behavior. The Ni-rich phase was verified to correspond to the " hexagonal phase in the Ni/GeSn system (Quintero et al, 2018b) as for the Ni/Ge system (DeSchutter et al, 2016). This latter is nonstoichiometric and can accept a wide range of Ge concentration between 35 and 44%; a similar behavior is expected for GeSn.…”
Section: Incorporation Of Sn Into the Intermetallicsmentioning
confidence: 93%
“…This shift was linked to stoichiometry variations (i.e. changes in GeSn concentration) in the "-Ni 5 (GeSn) 3 phase (Quintero et al, 2018b). This Nirich phase remained stable until 518 K, at which temperature the Ni(Ge 0.90 Sn 0.10 ) phase was sequentially obtained (see peaks at 34.2, 45.0, 53.9 and 87 ).…”
Section: Solid-state Reaction Overviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Different studies have evaluated the crystalline nature of the Ni-rich phase either on GeSn or SiGeSn substrates. The results showed that the Ni-rich phase corresponded to the hexagonal "-Ni 5 Ge 3 metastable phase (De Schutter, Van Stiphout et al, 2016;Quintero et al, 2018c). Meanwhile, in-depth studies concerning the texture of the monostanogermanide phase are not available.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of obtaining low resistive values when using nickel makes the contacts a key module to achieve high performance (Vincent et al, 2011;Demeulemeester et al, 2011;Han et al, 2011). Ni/Ge or Ni/GeSn contacts are formed by a solid-state reaction during which Ni 1Àx Ge x or Ni 1Àx (GeSn) x polycrystalline layers are obtained (Balakrisnan et al, 2005;Gaudet et al, 2006;De Schutter, Van Stiphout et al, 2016;van Stiphout et al, 2017;Nishimura et al, 2011;Wirths et al, 2014;Wirths, Geiger et al, 2015;Liu et al, 2015;Quintero et al, 2018c). In order to understand the properties of these polycrystalline films, it is essential to have a good understanding of their microstructure.…”
Section: Introductionmentioning
confidence: 99%